The Level of Organizational Performance of Sports Institutions in the United Arab Emirates - Mhamed, Kaabi; Qadhi, Assel; Djeddi, Rachad; Abderrahman, Abderraouf Ben (Advances in Social Sciences Research Journal, 2023)
The study aims to identify the level of organizational performance of the work of Emirati sports institutions from employees' point of view. The study relied on the descriptive analytical approach and a questionnaire as a tool for collecting data. The study sample consisted of (83) workers. The study reached several results, including: The level of organizational performance of the work of Emirati sports institutions from employees' point of view was moderate and does not meet aspirations to reach achievements at the Olympic level. Among the recommendations reached by the study is to give workers in Emirati sports institutions courses from international federations to develop their skills to keep pace with everything new in the science of sports management in order to ensure that sports institutions achieving their goals in the sports strategy for the year 2030 and working to establish projects that aims to adopt the sports talents of the youth to lead them to Asian and Olympic levels of competition